2021
DOI: 10.31372/20200504.1115
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Pain and Mood Disorders in Asian Americans

Abstract: Purpose: Pain and mood disorder frequently coexist. Yet, for Asian Americans (AAs), scant information about pain and mood disorder is available. Our aims were to compare (1) the rates of pain and mood disorders and (2) the magnitude of associations between pain and mood disorders between AAs and European Americans (EAs), and across different Asian subgroups. Methods: An analytical data was constructed from the Collaborative Psychiatric Epidemiology Studies (CPES), a representative sample of community-residing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…In those with chronic pain, Asian Americans demonstrated lower co-occurrence of mood disorders than European Americans. The study indicated the hypothesis of minority communities, particularly migrants, being more vulnerable to mood disorders and chronic pain may not always hold true [54].…”
Section: Race and Ethnicitymentioning
confidence: 92%
See 1 more Smart Citation
“…In those with chronic pain, Asian Americans demonstrated lower co-occurrence of mood disorders than European Americans. The study indicated the hypothesis of minority communities, particularly migrants, being more vulnerable to mood disorders and chronic pain may not always hold true [54].…”
Section: Race and Ethnicitymentioning
confidence: 92%
“…Both groups were not comparable in terms of sociodemographic variables, with European Americans being older and more likely to live alone than Asian Americans. Among Asian Americans, Vietnamese Americans showed stronger association between chronic pain and mood disorders than other Asian ethnicities, suggesting potential traumatic Vietnam War sequelae [54].…”
Section: Race and Ethnicitymentioning
confidence: 96%
“…Mood disorders, including depression and anxiety, are common health issues 22 . Pain and mood disorders frequently co-occur 17 , and chronic pain significantly increases the probability of mood disorders 23 . The combination of analgesics, psychotherapy and antidepressants can significantly relieve the symptoms of patients with chronic pain 16 , 23 25 .…”
Section: Introductionmentioning
confidence: 99%
“…Pain and mood disorders frequently co-occur 17 , and chronic pain significantly increases the probability of mood disorders 23 . The combination of analgesics, psychotherapy and antidepressants can significantly relieve the symptoms of patients with chronic pain 16 , 23 25 . Paroxetine is a typical serotonin-reuptake inhibitor (SSRI) used to treat a variety of mental health conditions including depression, anxiety disorders, obsessive–compulsive disorder, and post-traumatic stress disorder.…”
Section: Introductionmentioning
confidence: 99%